PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING PADA MATERI LIMIT FUNGSI DI SMA SWASTA BUDISATRYA MEDAN - Zulham Aditya; Bambang Irawan; Dhia Octariani (MES: Journal of Mathematics Education and Science, 2021)
This study discusses the development of the Student  Worksheets based on Problem Based Learning on the function limit material at the Private SMA Budisatrya Medan based on valid, practical, and effective criteria. The development on this learning device uses the Thiagarajan 4-D development model, in this study the writer only up to 3-D stage, namely: definition, design,  and development. The result of the research on the development of the Student Worksheets based on Problem Based Learning  on the function limit material at the Private SMA Budisatrya Medan fulfill the valid criteria based on the result of the assessment of 5 validators by filling out an assessment questionnaire with an average score of 3,9 and being in the good category, the are practically abtained through a student response questionnaire with an average score of 4,07 and are in the good category, and are effectively obtained through student learning outcomes tests with an average score of 75% and are in the good category.